Plasmodium falciparum Serine Repeat Antigen 5 (PfSERA5): current vaccine candidate for Plasmodium falciparum malaria - Ayuti Bulaan; W. Riski Widya Mulyani; Agung Nova Mahendra; I Wayan Sumardika (DiscoverSys Inc., 2020)
Background: Most of the malaria cases are caused by Plasmodium falciparum infection. The prevalence of cases and high mortality rates due to malaria should be watched out globally. However, currently, efforts to prevent and treat malaria suffer obstacles due to resistance to insecticides and antimalarial drugs. For these reasons, other preventive measures are needed, such as vaccines. This study aims to review the Plasmodium falciparum Serine Repeat Antigen 5 (PfSERA5) as a potential candidate for Plasmodium falciparum malaria vaccine development. Methods: Of the 65 journals reviewed, 51 journals were found to be suitable as references for this paper. The keywords included in selected search engines are